Blood neutrophils from children with COVID-19 exhibit both inflammatory and anti-inflammatory markers - Seery, Vanesa (2021)
Background: Perhaps reflecting that children with COVID-19 rarely exhibit severe respiratory symptoms and often remain asymptomatic, little attention has been paid to explore the immune response in pediatric COVID-19. Here, we analyzed the phenotype and function of circulating neutrophils from children with COVID-19. Methods: An observational study including 182 children with COVID-19, 21 children with multisystem inflammatory syndrome (MIS-C), and 40 healthy children was performed in Buenos Aires, Argentina. Neutrophil phenotype was analyzed by flow cytometry in blood samples. Cytokine production, plasma levels of IgG antibodies directed to the spike protein of SARS-CoV-2 and citrullinated histone H3 were measured by ELISA. Cell-free DNA was quantified by fluorometry. Findings: Compared with healthy controls, neutrophils from children with COVID-19 showed a lower expression of CD11b, CD66b, and L-selectin but a higher expression of the activation markers HLA-DR, CD64 and PECAM-1 and the inhibitory receptors LAIR-1 and PD-L1. No differences in the production of cytokines and NETs were observed. Interestingly, the expression of CD64 in neutrophils and the serum concentration of IgG antibodies directed to the spike protein of SARS-CoV-2 distinguished asymptomatic from mild and moderate COVID-19. Interpretation: Acute lung injury is a prominent feature of severe COVID-19 in adults. A low expression of adhesion molecules together with a high expression of inhibitory receptors in neutrophils from children with COVID-19 might prevent tissue infiltration by neutrophils preserving lung function.